THE DEVELOPMENT VARIATION MODELS OF PHYSICAL EXERCISE FOR BEGGINER FOOTBALLS ATHLETES - Denny Ariansyah (Sriwijaya University Learning and Education International Conference, 2018)
The purpose of this research is to develop a product in the form of variation of physical exercise model of football sport for beginner athlete. The method used in this research is the method of research and development which means developing a product or creating a new product. The population used is all students who follow football extracurricular in junior high school number 1 Palembang amounted to 17 people. Data collection technique in this research is pretest and posttest method by performing test before and after applying treatment of variation of exercise model. Technique of data analysis in this research use T-test. Based on result of output by using SPSS 16 that mean value from 17 tester that do test, test result before given model of exercise is 18.71 second and after given treatment with variation of model exercise 15.35 second, it means that the average value achieved by the speed increase in the time record. Based on the results of this study, it can be concluded that there are significant differences before and after being given treatment variation model physical exercise of football.